(3GdfXQGJ (B:s (3GdLRA GdKGdK eLehYI bUU (B/s - (3GdefadhWj, eUWai dWajs ((3GdLRGFQ (B:s (3ehae ddfTQh GdJhRjY (B;(3GdeDSSI GdhWfjI ddafhf GdeWHYjI ,s, 1988)
(3jfGOj GdefadhWj aj fXQJg HGdQMeI h GdEMSGS h YWa GdZfj Ydi GdabjQ h Gdbhj Ydi GdVYja h jUhQ GdYhGWa GdfHjdI h GdNUGd GdcajdI jESYGO GdeLJeY h jfOO HGdXde h GdCfGfjI h GfhGY GdaSGO h GdQPGFd h jHjf GfgG SHH GdHdGAs
Keywords: (3GdCOHs; (3GdEfJbGOs; (3GdefadhWjs